علاقة دوافع التعلم بنتيجة تعلم اللغة العربية لدى تلاميذ الصف الخامس بمدرسة الرحمة الابتدائية بسورابايا - Ganim, Saad bin Salim Ali; Santoso, Budi; Halim, Andy Fahmi (Thalaqah : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The purpose of this research is to find out the relationship between learning motivation and Arabic learning outcomes of SDIT Ar-Rahmah students. The purpose of this study is to provide input on the improvement in implementing Arabic language learning at SDIT Ar-Rahmah Surabaya, East Java.This study uses an associative quantitative method. The population of this study is 39 5th grade elementary school students, and for the sample of this study there are 39 5th grade elementary school students at SDIT Ar-Rahmah Surabaya, East Java. The data collection methods used are questionnaires, interviews and documentation. Instrument testing uses validity tests, and reliability tests. Correlation analysis of learning motivation with Arabic learning achievement using the Product Moment correlation test. Based on the results of the analysis, the significant level used at 5% with 39 respondents is 0.325. The correlation coefficient of the calculation is 0.1189, then it can be concluded that the calculation is smaller than the table, then the existing hypothesis is rejected. Therefore, it can be concluded that there is no significant relationship between learning motivation and student learning outcomes of SDIT Ar-Rahmah Surabaya, East Java for the 2023/2024 Academic Year.